Well-Being
XIV, 280 p.
Keywords: This interdisciplinary book indicates the need to address well-being from individual, community and social perspectives in an integrated manner. The book complements the harm-based focus of much social scientific research into health. Chapters by a wide range of academics present a new dynamic view of well-being for the Twenty-First Century.